(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
The paper focuses on personnel marketing, which treats employees like customers as part of an innovative approach in the field of human resource management. Using primary data, the work aims to identify attributes that lead to employee satisfaction. Collected from graduates of the Faculty of Economics at the Technical University of Liberec and businesses in the Liberec Region in 2016-2017, the results of primary research allow not only the identification of the most important attributes of satisfaction, but also a comparison of the results from the point of view of both employees and employers. Computer assisted web interviewing (CAWI) was employed as the data collection method. The outputs of the qualitative research represent knowledge important for recruiting employees and stabilising staff. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.